Product management for the enterprise : a practical introduction for project managers to building, managing, and scaling software for the enterprise (O'Reilly Media, 2017)
"Enterprise software product management is one of the most sought-after skills in technology today. This tutorial provides an insider's tip sheet on how to do this work with clarity and confidence. Whether you’re coming into PM from another business function, another field of software (like the consumer web), or from outside of the technology industry entirely, this course shows you exactly what you need to know to build, scale, and manage software products for the enterprise. You'll explore how PMs discover customer needs and pain points, gather market intelligence, and determine what needs to be built. You'll pick up the keys to working with your development and executive teams, and see why great product managers are not an organization’s sheepdogs, but their truth-tellers. You'll learn what success means for your product and how product managers should think about their future career plans."--Resource description page.